Short-Chain N-Acylhomoserine Lactone Quorum-Sensing Molecules Promote Periodontal Pathogens in In Vitro Oral Biofilms - Muras, Andrea (Appl Environ Microbiol, 2020)
Acylhomoserine lactones (AHLs), the quorum-sensing (QS) signals produced by a range of Gram-negative bacteria, are involved in biofilm formation in many pathogenic and environmental bacteria. Nevertheless, the current paradigm excludes a role of AHLs in dental plaque formation, while other QS signals, such as AI-2 and autoinducer peptides, have been demonstrated to play an important role in biofilm formation and virulence-related gene expression in oral pathogens. In the present work, we have explored the effect of externally added AHLs on in vitro oral biofilm models for commensal, cariogenic, and periodontal dental plaque. While little effect on bacterial growth was observed, some AHLs specifically affected the lactic acid production and protease activity of the biofilms. Most importantly, the analysis of bacterial diversity in the biofilms showed that the addition of C(6)-homoserine lactone (C(6)-HSL) results in a shift toward a periodontal bacterial composition profile by increasing the relative presence of the orange-complex bacteria Peptostreptococcus and Prevotella. These results point to a relevant role of AHL-mediated QS in dental plaque formation and might be involved in the development of dysbiosis, the mechanism of which should be further investigated. This finding potentially opens new opportunities for the prevention or treatment of the periodontal disease. IMPORTANCE Dental plaque is omnipresent in healthy oral cavities and part of our commensal microbial colonization. At the same time, dental plaque is the cause of the most common human diseases, caries and gum disease. Dental plaque consists of billions of microbes attached to the surface of your teeth. Communication among these microbes is pivotal for development of these complex communities yet poorly studied in dental plaque. In the present study, we show that a specific communication molecule induces changes within the community related to the development of gum disease. This finding suggests that interfering with microbial communication may represent an interesting novel strategy to prevent gum disease that should be further investigated.